Host plant odours enhance the responses of adult banana weevil to the synthetic aggregation pheromone Cosmolure+ - Tinzaara, William; Gold, Cliford S.; Dicke, M.; Huis, A. van; Ragama, P.E. (Informa UK Limited, 2007)
Attraction of adult banana weevil, Cosmopolites sordidus to volatiles from banana pseudostem tissue and the synthetic pheromone Cosmolure+ presented singly or in combination, was studied in the laboratory and in the field. Olfactometric studies in the laboratory showed that 50 g of fermented banana pseudostem tissue was as attractive as pheromone but more attractive than 50 g of fresh pseudostem tissue. In the laboratory, volatiles from pseudostem tissue had an additive effect on attraction of weevils to the pheromone but the effect was not significant in the field. Field trials, however, showed that attractiveness to weevils was positively correlated with the amount of fermented tissue added to the pheromone. The results indicate that fresh or fermented pseudostem tissue may enhance pheromone trap catches but the effect was not large enough to warrant their deployment for the optimisation of the infochemical-based trapping system for the management of C. sordidus.